"Open strategic autonomy": An assessment and positioning for German development policy - Stephan Klingebiel (German Institute of Development and Sustainability (IDOS), 2024)
"This policy brief provides an overview and assessments of debates on development policy. In view of changing international contexts, it addresses the need to reorient German development policy in the long term and initiate reforms. Five recommendations for decision-makers are formulated: 1. "Open strategic autonomy" for development policy: Development policy should play an independent and complementary role when supporting partners from the Global South and providing global public goods. "Open strategic autonomy" could integrate different policy areas and actors, but at the same time maintain a certain degree of autonomy in order to act effectively. 2. Redefining goals: Development policy is often seen as purely altruistic and humanitarian, but it should rather be understood as a soft power instrument. Such an understanding could help to break away from the restrictive discourse on values and interests. 3. Interface management and ministerial customisation: There are debates about coordination between ministries and whether an independent development ministry (BMZ) is necessary. More effective interface management and the bundling of humanitarian aid and development cooperation could increase efficiency and effectiveness. The current coalition agreement provides for greater coordination of development policy funds, but progress so far has been limited. In principle, there are reasons in favour of an independent development policy department in Germany. 4. Strategic orientation during implementation: Policy-based financing should play a greater role in order to provide more comprehensive support for reforms and transformations. It is advisable to switch from supply-orientated to demand-orientated development cooperation. By critically scrutinising tied services, competition and choice for partner countries can be strengthened. As is shown by the Just Energy Transition Partnerships and the European Global Gateway Initiative, more new solutions are needed. 5. Dealing with populist and right-wing nationalist movements: Development policy is increasingly under attack from right-wing and populist movements. These attacks are intended to undermine social consensus. In response, these attacks can be ignored or the bogus arguments can be invalidated. In order to counter the changed situation, the democratic parties in the German Bundestag should strive for a new cross-party consensus on development policy. To summarise, it is necessary to focus less on the populist project-related debates. What is needed is a more strategic and long-term perspective on development policy that systematically integrates various political and social interests and offers the prospect of flexible and partnership-based implementation.
Keywords: 320; Development cooperation; development policy; Germany; populism; Global South; geopolitics; geoeconomics; climate finance; migration; Federal Ministry for Economic Cooperation and